An analysis on distribution and inter-relationships of biomarkers under rivaroxaban in Japanese patients with non-valvular atrial fibrillation (CVI ARO 1). Issue 4 (August 2018) - Suzuki, Shinya; Yamashita, Takeshi; Kasai, Hidefumi; Otsuka, Takayuki; Sagara, Koichi
Abstract: Prothrombin time (PT) has been widely used for measuring anticoagulation intensity under rivaroxaban therapy, but precise information has not been well established yet. Consecutive 96 non-valvular atrial fibrillation (NVAF) under rivaroxaban between Jan/June, 2015 were recruited. Serum concentration (SC) and PT with 5 representative reagents available in Japan (Neoplastin Plus®, Thromborel S®, Thrombocheck PT®, Thrombocheck PT Plus®, and Recombiplastin®) at 2-4 hours after (peak) and before intake of rivaroxaban (trough) were measured at outpatient clinic in the cardiovascular institute (CVI ARO study 1). Nonlinear mixed-effects modelling was used to model the population pharmacokinetics and pharmacodynamics of rivaroxaban. An oral one-compartment model was employed to describe the population pharmacokinetics of rivaroxaban. The pharmacokinetics of rivaroxaban were affected by creatinine clearance, alanine aminotransferase, and use of CYP3A4 or P-gp inhibitors. PTs with 5 reagents were predicted by pharmacodinamic models with SC, hematocrit, serum albumin, and age, with medium predicting ability (highest/lowest R2 = 0.746/0.658 in Recombiplastin/Thromborel S, respectively). This population analysis in NVAF patients under rivaroxaban therapy demonstrated that pharmacokinetics of rivaroxaban was described by an oral one-compartment model with expected covariates, and can be assessed by PT with available reagents in Japan with medium predicting ability. Graphical abstract: